Even pacing is superior to intermittent pacing in competitive cross-country cyclists during a ~ 6 min work-matched time to exhaustion protocol - Vaule, L. (Norwegian School of Sport Sciences, 2024)
Purpose: Existing literature proposes an even-pacing strategy as the optimal approach for best performance during prolonged endurance events (>2 minutes) but lacks support of systematic experimental data. This study tested the hypothesis that even-paced cycling is superior to intermittent-paced cycling during a time to exhaustion protocol on a bike trainer at 100 % of maximal aerobic power (MAP).